Legal basis for the activity of the temporary work agency - Spytek-Bandurska, Grażyna (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The aim of the article is to present the legal basis for the functioning of temporary employment agencies. Their specificity lies in the fact that they are economic entities and at the same time labour market institutions. The services provided by the agencies constitute a regulated activity and are subject to many administrative requirements, which have been discussed in detail by the Author. A distinguishing property of agencies is temporary work classified as an atypical form of employment, due to the characteristic features assigned to it, mainly the tripartite legal structure and limited duration, which are presented later in this article.